Protective Effect of Traditional Medicine Tagtaggunsel on Carbon Tetrachloride Induced Chronic Liver Cirrhosis in a Rat Model - Tsogtoo Bukhbayar; Dejidmaa Buyantogtokh; Chimedragchaa Chimedtseren; Badamsuren Dorjgotov (Central Asian Journal of Medical Sciences, 2018)
Objective: To study the effect of traditional medicine tagtaggunsel on the development of chronic cirrhosis in rat model. Methods: Rats were divided into 4 groups of 18 animals each. Group I served as the normal healthy control, groups II rats were intoxicated with carbon tetrachloride subcutaneous by injection (0.1 ml/kg body weight carbon tetrachloride /olive oil, three times per week for 12 weeks), group III rats received carbon tetrachloride intraperitoneally plus tagtaggunsel orally (100 mg/kg daily) and group IV rats received carbon tetrachloride intraperitoneally plus Silymarin orally (50 mg/kg daily). The hepatoprotective potential of tagtaggunsel in rats was evaluated by measuring the enzyme levels of ALT, AST and serum iron, ferritin, hepcidin in addition to other liver biomarkers. Histopathological changes in the liver were assessed using hematoxylin and eosin, Masson-trichrome staining. Results: The administration of tagtaggunsel showed hepatic protection at an oral dose of 100 mg/ kg. tagtaggunsel significantly reduced the elevated serum levels of liver enzymes as well as liver biomarkers in comparison to carbon tetrachloride−intoxicated group. Notably, tagtaggunsel significantly reduced the expression level of ferritin, but hepcidin significantly increased compared to their levels in carbon tetrachloride intoxicated group. These findings were confirmed with the histopathological observations, where tagtaggunsel was capable of reversing the toxic effects of carbon tetrachloride on liver cells compared to that observed in carbon tetrachloride-intoxicated rats. Conclusion: Our results show that tagtaggunsel has potential hepatoprotective effects at 100 mg/ kg. These effects can be regarded as antioxidant properties of the extract.